Modular palladium bipyrazoles for the isomerization of allylbenzenes - mechanistic considerations and insights into catalyst design and activity, role of solvent, and additive effects - Spallek, Markus Jürgen; Stockinger, Skrollan Carina; Trapp, Oliver (Advanced synthesis & catalysis, 2012)
The catalytic activity of novel bidentate N,N-chelated palladium complexes derived from electron excessive, backbone fused 3,3′-bipyrazoles in the selective isomerization of terminal arylpropenoids and 1-alkenes is described. The catalysts are easily modified by appropriate wing tip substitution, while maintaining the same bulky, rigid unreactive aliphatic backbone. Eleven novel palladium complexes with different electronic and steric properties were investigated. Their performance in the palladium(II)-catalyzed isomerization of a series of substituted allylbenzenes was evaluated in terms of electronic as well as steric effects. Besides the clear finding of a general trend towards higher catalyst activity with more electron-donating properties of the coordinated N,N-bidentate ligands, we found that the catalytic process strongly depends on the choice of solvents and additives. Extensive solvent screening revealed that reactions run best in a 2:1 toluene-methanol mixture, with the alcohol employed being a crucial factor in terms of electronic and steric factors. A reaction mechanism involving a hydride addition-elimination mechanism starting with a palladium hydride species generated in situ in alcoholic solutions, as corroborated by experiments using deuterium labeled allylbenzene, seems to be most likely. The proposed mechanism is also supported by the observed reaction rate orders of κobs[cat.]≈1 (0.94), κobs [substrate]=0.20→1.0 (t→∞) and κobs [methanol]=−0.51 for the isomerization of allylbenzene. Furthermore, the influence of acid and base, as well as the role of the halide coordinated to the catalyst, are discussed. The system catalyzes the isomerization of allylbenzenes very efficiently yielding high E:Z selectivities under very mild conditions (room temperature) and at low catalyst loadings of 1 mol% palladium even in unpurified solvents. The integrity and stability of the catalyst system were confirmed by multiple addition reaction cycles, successive filtration and isolation experiments, and the lack of palladium black formation.